PENGALAMAN MEREK DESTINASI SEBAGAI MEDIATOR TERHADAP LOYALITAS MEREK DESTINASI - Tarigan, Miska Irani; Parhusip, Poltak T. (Jurnal Manajemen dan Bisnis, 2022)
Outside of the oil and gas sector, tourism is one of the mainstay sectors for Indonesia's foreign exchange earnings. The Indonesian government has devised a long-term strategy to develop ten destinations outside of Bali, and the Lake Toba Tourism Area is one of the National Tourism Strategy Areas (KSPN) that is geared toward international expansion. Tourism marketing has expanded dramatically in recent decades. After a long period of recovery from the Pandemic, the tourism industry is back on its feet. The applied theory in this study is brand experience-based tourism marketing.This study investigates the hypothesis of several brand experience factors at destinations, including Destination Image, Infrastructure and Support Services at Destinations, and Attractions at Destinations, and investigates their influence on destination brand loyalty. In this study, the population consisted of domestic tourists who visited the tourist area of Lake Toba in North Sumatra. The sampling technique used is non-probability sampling, specifically purposive sampling, and sample distribution with quota sampling. This study includes 40 indicators and 200 participants.SmartPLS was used to process respondent data, which was then analyzed using the Structure Equation Model (SEM). In this study, seven hypotheses are tested. The Destination Brand Experience is positively influenced by the Destination Image, Infrastructure and Supporting Services at the Destination, and Attractions at the Destination. Similarly, Destination Brand Experience influences Destination Brand Loyalty positively and significantly. Destination Brand Experience has a significant positive effect on Destination Brand Loyalty as a moderator between Destination Image, Infrastructure and Supporting Services at Destinations, and Attractions at Destinations.